2012
DOI: 10.1080/02640414.2012.707327
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal dynamics and relative positioning to scoring target of performers in 1 vs. 1 sub-phases of team sports

Abstract: In this study, we examined the effects of relative positioning of attacker-defender dyads to the basket on interpersonal coordination tendencies in basketball. To achieve this aim, four right-hand dominant basketball players performed in a 1 vs. 1 sub-phase, at nine different playing locations relative to the basket (from 0° to 180°, in 20° increments). Performers' movement displacement trajectories were video-recorded and digitized in 162 trials. Results showed that interpersonal coordination tendencies chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Indeed, interaction patterns in team sports have been previously investigated in a different perspective (Vilar, Araujo, Davids, & Button, 2012), in which the formation of playing patterns was analyzed through the dynamics of both single (Correia et al, 2012;Esteves et al, 2012) and multiple offensive-defensive couples of players (Corrêa, Vilar, Davids, & Renshaw, 2012;Duarte et al, 2012). In these studies, the assessment of offense-defense dynamics was used as a framework to determine players' decision process.…”
Section: Spds Validationmentioning
confidence: 99%
“…Indeed, interaction patterns in team sports have been previously investigated in a different perspective (Vilar, Araujo, Davids, & Button, 2012), in which the formation of playing patterns was analyzed through the dynamics of both single (Correia et al, 2012;Esteves et al, 2012) and multiple offensive-defensive couples of players (Corrêa, Vilar, Davids, & Renshaw, 2012;Duarte et al, 2012). In these studies, the assessment of offense-defense dynamics was used as a framework to determine players' decision process.…”
Section: Spds Validationmentioning
confidence: 99%
“…It has been suggested that fi eld positioning of attacker-defender pairs and their proximity to fi xed informational constraints for decision-making and action (such as baskets) may be considered important in stabilizing players' behaviours and an environmental constraint in the symmetrybreaking behaviour of attackers [ 28 , 42 ] . Furthermore, a recent study demonstrated that the attacker's relative position to the basket may infl uence the outcome of the attacker-defender interaction [ 10 ] . Therefore, both team and opponents' baskets seem to be an important informational constraint to provide a stable and rational reference to space-time distribution during the game.…”
mentioning
confidence: 99%
“…In basketball (Bourbousson, S eve, & McGarry, 2010;Esteves et al, 2012) and football (Duarte et al, 2012;Duarte et al, 2010), players matched up with each other tend to move the same direction of the long axis of the court. In these sports, players perceive the directions, velocities, and distance of the ball, goals, teammates, and opponents in relation to themselves and control and coordinate their relative distance from these targets (Clemente, Couceiro, Martins, Dias, & Mendes, 2013;Cordovil et al, 2009;Esteves, de Oliveira, & Ara ujo, 2011;Passos et al, 2011;Travassos et al, 2012;Vilar, Ara ujo, Davids, & Button, 2012). In many group ball games, it is important for players to continually perceive the position and displacement of many objects and affordances for their own and others' athletic ability and to rapidly change their relative distances to these targets based on task constraints and goals.…”
Section: Affordance Perception and Distance Maneuvers In Sportsmentioning
confidence: 99%